2021
DOI: 10.1186/s43045-021-00092-x
|View full text |Cite
|
Sign up to set email alerts
|

Depression and psychosocial burden among caregivers of children with chronic kidney disease

Abstract: Background More attention has recently targeted families of children with chronic kidney diseases displaying depressive symptoms and major psychosocial burden due to the long-standing nature of the illness and its alarming complications. A cross sectional comparative study was conducted to assess the rate of occurrence of both depression severity and psychological burden, personal and role strain in a sample of Egyptian caregivers of children with chronic kidney disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…Of note, in advanced CKD, quality of life is worse in women than in men 107 . Moreover, having a person with CKD in the family adversely impacts the mental health of caregivers, 30-50% of whom report symptoms of anxiety or depression [110][111][112][113] .…”
Section: Kidney Disease Carries High Morbidity and Mortalitymentioning
confidence: 99%
“…Of note, in advanced CKD, quality of life is worse in women than in men 107 . Moreover, having a person with CKD in the family adversely impacts the mental health of caregivers, 30-50% of whom report symptoms of anxiety or depression [110][111][112][113] .…”
Section: Kidney Disease Carries High Morbidity and Mortalitymentioning
confidence: 99%
“…Caregivers of children with CKD are burdened with the responsibility of keeping up with numerous appointments, ensuring adherence to (often multiple) medications, monitoring diet and fluid restrictions, performing time-consuming and involved technical procedures such as home dialysis, and advocating for their child's health care needs [8]. Consequently, caregivers may experience high levels of physical and psychosocial stress [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Prior work has shown that children with CKD whose caregivers are unemployed, have lower incomes, poorer selfperceived financial status and lack of home ownership are at least twice as likely to experience poor to fair overall health compared to children with more affluent caregivers [14,15]. Health inequities in these children are likely to reflect multiple factors including poor access to primary or specialty care, complex health care systems, rigorous and burdensome treatment regimens, lack of awareness of resources, and geographic and language barriers [9][10][11]17]. The quality of care that these children receive are further influenced by the conflicting priorities and psychosocial stressors faced by the caregivers that can be related to depleting resources caused by continual medical treatment, fatigue and exhaustion from the burden of caring, the demands of tending to family members (e.g., siblings of the patient), and providing financial support to the family [9,18].…”
Section: Introductionmentioning
confidence: 99%
“…Intervensi kesehatan masyarakat harus dikembangkan dan diimplementasikan untuk meningkatkan kualitas hidup pasien GGK (Mahato, 2020). Terjadi peningkatan kejadian depresi dan beban psikologis secara signifikan tinggi pada Caregiver anak-anak dengan penyakit ginjal kronis (Mahmoud, 2021). Hasil penelitian di atas menujukan bahwa begitu pentingnya peran dari keluarga pasien dengan GGK yang menjalani hemodialisis, peran ini hendaknya jangan menjadi beban bagi keluarga sebagai caregiver, maka tujuan penelitian ini adalah untuk mengetahui hubungan lama merawat dan tingkat pendidikan dengan beban keluarga sebagai caregiver dalam merawat pasien penyakit ginjal kronik yang menjalani hemodialisis.…”
unclassified